Becoming the boss : new rules for the next generation of leaders / Lindsey Pollak - Pollak, Lindsey
We are in the midst of a leadership revolution, as power passes from Baby Boomers to Millennials. All grown up, the highly educated Generation Y is moving into executive positions in corporations and government, as well as running their own businesses, where they are beginning to have a profound impact that will last for decades. Pollak provides a brisk, tech savvy success manual filled with real-world, actionable tips. Discover the key trends affecting your career, and master the classic rules of excellence that never go out of style.